Rekonstrukce železniční tratě Bludov - Hanušovice mezi km 56,165 a km 59,105 včetně návrhu technologie prací - Hlavová, Vendula (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Bakalářská práce se zabývá úpravou geometrických parametrů koleje a návrhem vhodné skladby železničního svršku v úseku železniční tratě Bludov – Hanušovice. Při návrhu jsou zohledněny stávající objekty a to, propustky, přejezd, nástupiště a mostní objekty. V rámci celé práce je řešen návrh odvodnění tratě, technologie provádění prací a také snaha o zvýšení traťové rychlosti.

The bachelor thesis deals editing track geometry parameters and design appropriate track railway superstructure in a section of railway Bludov – Hanušovice. The design should be considered primarily on existing objects as culverts, railway crossing, railway stops, and bridges. Thesis includes restoration of drainage, track laying technology and efforts to incease the track speed.
Bludov - Hanusovice Railway Track Reconstruction (section between km 56.165 - km 59.105) Including Track Laying Technology
Keywords: Geometrické parametry koleje; osa koleje; rozchod koleje; kolejnice; kolejové lože; železniční svršek; železniční spodek; železniční přejezd; nástupiště; příkopová zídka.; Track geometry parameters; centre-line of track track gauge; balast bed rails; permanent way; railway crossing; platform; rift wall.